2020
DOI: 10.1111/acer.14489
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Alcohol‐Exposed Pregnancies and Fetal Alcohol Spectrum Disorder Among Pregnant and Postpartum Women: A Systematic Review

Abstract: Background: Prenatal alcohol exposure can result in a wide range of adverse health outcomes, including in some cases fetal alcohol spectrum disorder (FASD), a lifelong neurodevelopmental disorder. Thus, there is pressing need for effective interventions to prevent alcohol-exposed pregnancies (AEPs). Methods: A systematic review was undertaken to provide an up-to-date analysis of the current prevention literature. PubMed, Embase, CINAHL, and PsycINFO were searched for relevant English-language articles publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 77 publications
(254 reference statements)
1
17
0
Order By: Relevance
“…The current review did not identify any interventions that included consideration of a woman's partner or wider social context (e.g., family members or friends) as a part of the intervention. This is also consistent with the recent review of pregnancy interventions (Erng et al, 2020), which also noted limited focus on wider contextual factors, which may maintain alcohol use and, in this case, may contribute to contraceptive decision making. For instance, Montag et al (2019) found that alcohol use in women of reproductive age within a Southern California American Indian community was strongly influenced by female friends and relatives.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The current review did not identify any interventions that included consideration of a woman's partner or wider social context (e.g., family members or friends) as a part of the intervention. This is also consistent with the recent review of pregnancy interventions (Erng et al, 2020), which also noted limited focus on wider contextual factors, which may maintain alcohol use and, in this case, may contribute to contraceptive decision making. For instance, Montag et al (2019) found that alcohol use in women of reproductive age within a Southern California American Indian community was strongly influenced by female friends and relatives.…”
Section: Discussionsupporting
confidence: 89%
“…Hand‐searching of reference lists yielded an additional 9 relevant studies, resulting in a total of 53 eligible studies. Of these, 19 focused on women who were not pregnant (the current review) and 34 focused on pregnant or postpartum women (Erng et al, 2020). No additional studies were identified from an updated search completed prior to submission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suggesting that the male drinking patterns also need to be addressed in relation to pregnancy is vital to successfully expanding the conversation on prevention. This would serve to move the issue from a "women's" issue to one that involves men and women [56] This expands the economic implications for the industry.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, multiple systematic reviews and meta-analyses have examined the effectiveness of digital interventions for smoking cessation [ 13 - 15 ]. Only systematic reviews on the effectiveness of nondigital interventions for preventing alcohol consumption during pregnancy, such as cognitive-behavioral therapy and motivational interviewing [ 16 - 19 ], were found in our analyses. By contrast, a number of reviews examined the effectiveness of digital and computer-based alcohol intervention programs in primary care [ 20 , 21 ] or for patients recovering from substance use disorders [ 22 , 23 ], but such studies did not target pregnant women or women planning to become pregnant.…”
Section: Introductionmentioning
confidence: 99%